Model for the determination of instantaneous values of the velocity, instantaneous, and average acceleration for 100-m sprinters - Janjic, N. J.; Kapor, D. V.; Doder, D. V.; Doder, R. Z.; Savic, B. V. (The Journal of Strength and Conditioning Research, 2014)
Temporal patterns of running velocity is of profound interest for coaches and researchers involved in sprint racing. In this study, we applied a nonhomogeneous differential equation for the motion with resistance force proportional to the velocity for the determination of the instantaneous velocity and instantaneous and average acceleration in the sprinter discipline at 100 m. Results obtained for the instantaneous velocity in this study using the presented model indicate good agreement with values measured directly, which is a good verification of the proposed procedure. To perform a comprehensive analysis of the applicability of the results obtained, the harmonic canon of running for the 100-m sprint discipline was formed. Using the data obtained by the measurement of split times for segments of 100-m run of the sprinters K. Lewis (1988), M. Green (2001), and U. Bolt (2009), the method described yielded results that enable comparative analysis of the kinematical parameters for each sprinter. Further treatment allowed the derivation of the ideal harmonic velocity canon of running, which can be helpful to any coach in evaluating the results achieved at particular distances in this and other disciplines. The method described can be applied for the analysis of any race.